Towards the definition of a solar forcing dataset for CMIP7 - B. Funke; T. Dudok de Wit; T. Dudok de Wit; I. Ermolli; M. Haberreiter; D. Kinnison; D. Marsh; D. Marsh; H. Nesse; A. Seppälä; M. Sinnhuber; I. Usoskin; et al. (Geoscientific Model Development, 2024)
The solar forcing prepared for Phase 6 of the Coupled Model Intercomparison Project (CMIP6) has been used extensively in climate model experiments and has been tested in various intercomparison studies. Recently, an International Space Science Institute (ISSI) working group has been established to revisit the solar forcing recommendations, based on the lessons learned from CMIP6, and to assess new datasets that have become available, in order to define a road map for building a revised and extended historical solar forcing dataset for the upcoming Phase 7 of CMIP. This paper identifies the possible improvements required and outlines a strategy to address them in the planned new solar forcing dataset. Proposed major changes include the adoption of the new Total and Spectral Solar Irradiance Sensor (TSIS-1) solar reference spectrum for solar spectral irradiance and an improved description of top-of-the-atmosphere energetic electron fluxes, as well as their reconstruction back to 1850 by means of geomagnetic proxy data. In addition, there is an urgent need to consider the proposed updates in the ozone forcing dataset in order to ensure a self-consistent solar forcing in coupled models without interactive chemistry. Regarding future solar forcing, we propose consideration of stochastic ensemble forcing scenarios, ideally in concert with other natural forcings, in order to allow for realistic projections of natural forcing uncertainties.